The impact of public spending on the inflation rate in Algeria: an econometric study for the period 2000-2023 - Yassine MOSTEFAI; Chafik BOUBERRIMA (Theoretical and Applied Economics, 2025)

(untitled)
The study aims to measure the impact of public spending on the inflation rate in Algeria using time series data in the period 2000-2023, obtained from World Bank data. The Autoregressive Distributed Lag Bounds Test (ARDL) methodology is applied to achieve the study’s objectives. The short-run results indicate that inflation is positively affected by lagged public spending by one and two lags, with an adjustment speed toward equilibrium of 1.59. In the long run relationship, the findings reveal that public spending has a positive and statistically significant effect on inflation. Based on these results, the study recommends reducing government subsidies and redirecting public spending toward productive projects that promote infrastructure and economic growth.